MATHEMATICAL MODELING AND SENSITIVITY ANALYSIS OF LINEAR CONSECUTIVE 2:3:: G SYSTEM - Oberoi, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this paper, reliability modelling and sensitivity analysis are applied to two of the three cold standby systems, an external supporting system with preventive maintenance, and a single server that is susceptible to failure. Two of the three units are used in this study so that the system is functioning at its most efficient level when all three are in use. A faultless switchover mechanism helps turn on the third unit, which is in cold standby mode. These online and offline units are operated by the supporting system, which also manages a repair facility with a model for dependability performance measurements and supervises preventative maintenance for all kinds of units. Regarding the starting and base states, a large number of primary, secondary, and tertiary circuits, base states, and simple paths are provided. RPGT is used to represent four reliability measures with various path probabilities, transition probabilities, mean sojourn periods, and expressions, maintaining one of the facility unit failure or repair rates while altering the other. After that, sensitivity analysis is carried out by making the relevant tables and graphs and having a conversation.